2020
DOI: 10.1186/s12887-020-02203-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profiles and drug susceptibility of Streptococcus isolated from conjunctival sac of healthy children

Abstract: Background: To investigate bacterial flora and antibiotics susceptibility of Streptococcus pneumoniae isolated from the conjunctival sac of heathy children. Methods: Bacteria were isolated from the secretions of conjunctival sac of healthy children between 2015 and 2018. Antimicrobial susceptibility of isolated S. pneumoniae strains were determined using microbroth dilution method. Results: The sac secretions were collected from a total of 6440 children. 1409 samples presented bacterial growth, accounting for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 29 publications
(29 reference statements)
0
11
4
Order By: Relevance
“…Furthermore, in a prospective observational study among patients undergoing cataract surgery in the USA, Ta et al showed that almost eight of every ten ocular specimen obtained from patients eyes had a bacteria etiology 26 . On the one hand, estimates from the present study is signi cantly higher and varies substantially compared to studies in China 13,18 , Iran 20 , South Korea 14 and Nepal 15 with prevalence estimates far lower than 50% [13][14][15]18,20 . Although geographical settings, study population, seasonality and laboratory procedures could account for such variations as reported earlier, a plausible reason for our observation may be attributable to the fact that our study unlike previous investigations enrolled patients from multiple eye care facilities hence the burden of infections maybe summative.…”
Section: Bacteria Etiology Of External Ocular and Periocular Infections Among Study Participantscontrasting
confidence: 81%
See 3 more Smart Citations
“…Furthermore, in a prospective observational study among patients undergoing cataract surgery in the USA, Ta et al showed that almost eight of every ten ocular specimen obtained from patients eyes had a bacteria etiology 26 . On the one hand, estimates from the present study is signi cantly higher and varies substantially compared to studies in China 13,18 , Iran 20 , South Korea 14 and Nepal 15 with prevalence estimates far lower than 50% [13][14][15]18,20 . Although geographical settings, study population, seasonality and laboratory procedures could account for such variations as reported earlier, a plausible reason for our observation may be attributable to the fact that our study unlike previous investigations enrolled patients from multiple eye care facilities hence the burden of infections maybe summative.…”
Section: Bacteria Etiology Of External Ocular and Periocular Infections Among Study Participantscontrasting
confidence: 81%
“…We observed a slightly higher proportion of Gram-negative bacteria compared to Gram positives as etiological agent in our study. This ndings contrast with studies from China 13 , Ethiopia 11 , Saudi-Arabia 16 , Uganda 4 and United States of America 26 where Gram negatives were found to be signi cantly lower compared to Gram positive bacteria and with proportional estimates of ranging from six to ten percent 4,11,13,16,26 . Conversely, the proportionate distribution of Gram negatives to positive bacteria found in this study are parallel with results from several existing literatures 2,5,8,10 .…”
Section: Bacteria Etiology Of External Ocular and Periocular Infections Among Study Participantscontrasting
confidence: 57%
See 2 more Smart Citations
“…The conjunctiva is the mucous membrane that lines the internal aspect of the eyelids and extends to the orbital globe, and the conjunctival sac is the space bound between the palpebral and bulbar conjunctiva 1 . Given its continuous exposure to the outside environment, the normal commensal ora and potential pathogens can be detected in the conjunctival sac 2 .…”
Section: Introductionmentioning
confidence: 99%